Imam Ash’ari‘s Moderate Theological Approach - Al Azhari, Abdul Wahab Jan (Journal of Islamic and Religious Studies, 2017)
Although the Muslim theological schools have tried to relate their ideologies to the companions of the Prophet (Peace be upon him), the Asha’arah stressed upon this the most so as to ensure that their school of thought remains attached to the Sunni creed. Al- Ash’ari in his school and approach, always tried to keep the middle way between the Ḥanbali and M’utazili approaches, and tried to stay connected to the way of the Salaf or early generations. His moderation in approach lied in his accommodative attitude towards Sunnah as well as incorporating reason in his thought, whence he tried to avoid the two extremes followers by M’utazilah and Hanabilah, pure reason and pure tradition, in issues like God’s attributes, creation of Quran and others. The present paper tries to highlight the main features of Al- Ash’ari ’s moderate theological approach.